Exploring the mediating factors linking adverse childhood experiences to traditional Chinese quality of life among older adults: a multi-factorial analysis - Sun, Mingjun; Zhang, Na; Zhang, Yuxin; Chang, Wurong; Cao, Haolin; Zhou, Qiang; Li, Limin; Tang, Zijian; Zhou, Yulu; Li, Huiwen; Yao, Yisong; Si, Junxiao (Frontiers in Public Health, 2025)
PurposeThe global population is aging rapidly, making the facilitation of positive aging a pivotal issue that necessitates immediate global attention. This study investigates the association between adverse childhood experiences (ACEs) and the Chinese medicine quality of life (CMQL) in older adults, guided by life course theory and a traditional Chinese medicine perspective.MethodsA total of 1,119 older adults individuals were included in this study. Logistic regression and propensity score matching (PSM) were used to explore the relationship between ACEs and CMQL. Structural equation modeling was employed to analyze the mediating roles of balance constitution, chronic disease, and perceived social support in the relationship between ACEs and CMQL.ResultsThere was a significant negative association between ACEs and CMQL among older adults. Individuals with ACEs displayed compromised balance constitution, a higher prevalence of chronic diseases, and a lower level of CMQL. High levels of perceived social support were identified as a protective factor, effectively mitigating the adverse effects of ACEs on CMQL among older adults individuals.ConclusionWhile the study uncovered a significant negative correlation between ACEs and CMQL in older adults, it is important to acknowledge the limitations of drawing causal relationships from cross-sectional data. Moreover, the findings underscore the protective role of perceived social support in mitigating the detrimental impacts of ACEs on CMQL in the older adults population. Therefore, prioritizing interventions that bolster social support networks may offer significant benefits in enhancing the overall quality of life for older adults.